Lumbar (L4) Intradural Motor Nerve Root Repair Using Collagen Tube Following Excision of Schwannoma: First Case Report - Bassam M. Addas; Rakan F. Bokhari; Rajiv Midha (Journal of King Abdulaziz University: Medical Sciences, 2023)
A report on a 38-year-old woman presented with intradural L4 nerve sheath tumor, causing progressive low back and right leg pain for 5 months duration. Intra-operatively, the tumor was found to arise from the entire extent or at least a sizable portion of the L4 spinal motor nerve root. This was confirmed by intra-operative electromyography which demonstrated contraction of both tibialis anterior and vastus medialis. Microanatomical separation of the involved nerve and the tumor was not possible. The proximal and the distal end of the fascicle were resected with the tumor. Primary repair of the transected nerve was not possible. A collagen nerve tube measuring 1.5 cm was used to bridge the gap. At a 4 year follow up, the patient did not have any sensory complaints or functional impairment. This case illustrates the safety of using a nerve guidance tubes in repairing short injury gaps in cauda equina motor nerve roots.